Peranan Organisasi Sekaa Teruna Teruni Sebagai Media Komunikasi Kepemudaan Hindu - I Nyoman Ariyoga (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
Bali as one of the paradise of the world has a solution that has been run from generation to generation by previous ancestors. The existence of Sekaa Teruna Teruni (STT) is quite a pillar to support the rampant globalization storm that is hitting young people today. Sekaa Teruna Teruni comes from the word sekaa, which means association, organization, while teruna teruni is the Indonesian word for young women. So, Sekaa Teruna Teruni is a collection, container, social organization for the development of young people who grow and develop on the basis of social awareness and responsibility. STT is a Hindu youth communication media which is related to the benefits of public communication in the Sekaa Teruna Teruni organization, the relevance of Sekaa Teruni Teruni to the demands of the current era, the benefits of Sekaa Teruna Teruni in the development of character and culture, and factors that impede the application of communication in Sekaa Teruna Teruni. STT will gain a lot of new experiences, through their organization they will also know how to communicate well with others, learn to work together with others, and most importantly young women can know, understand and deal with different people's characters. Become an agent of change and maintain the cultural traditions around the neighborhood, which is the identity of each banjar, village and the island of Bali.